PENERAPAN MODEL PEMBELAJARAN ADVANCE ORGANIZER BERVISI SETS TERHADAP PENINGKATAN PENGUASAAN KONSEP KIMIA - Pratitis, Ilam; Binadja, Achmad (Jurnal Inovasi Pendidikan Kimia, 2014)
This study aims to determine the effect of the application of learning model with advance organizer envisions SETS to increase mastery of chemistry concepts in the high school in Semarang on buffer solution material. The design used in this research is the design of the control group non equivalent. Sampling was conducted with a purposive sampling technique, and obtained a XI 6 science grade as experimental class and class XI 5 science grade as control class. Data collection method used is the method of documentation, testing, observation, and questionnaires. The results showed that the average cognitive achievement of experimental class was 84, while the control class was 82. The result of data analysis showed that the effect of the application of learning model with advance organizer envisions SETS was able to increase the mastery of chemical concepts of 4%, with a correlation rate of 0.2. Based on the results, it can be concluded that the learning model with advance organizer envisions SETS had positive effect of increasing mastery of the concept of chemistry on buffer solution material. The advice given is learning model with organizer envisions SETS should also beÂ applied to other chemistry materials. This is of course accompanied by a change in order to suit the needs of its effect on learning outcomes in the form of concept mastery of chemistry to be more increased.Keywords: Advance Organizer, Buffer Solution, Concept Mastery, SETS